PERFORMA BUDIDAYA BENIH IKAN TAMBAKAN (Helostoma temminckii) DENGAN KEPADATAN BERBEDA PADA SISTEM RESIRKULASI - Emilda Dwi Santi; Ferdianand Hukama Taqwa; Retno Cahya Mukti (Jurnal Akuakultur Rawa Indonesia, 2021)
The kissing gourami (Helostoma temminckii) is a freshwater fish with high economic value, so it has a high potential for cultivation. However, increasing fish stocking density in aquaculture can result in a decrease in water quality in the culture media. A recirculation system is one solution for overcoming the decline in water quality caused by high fish density. The purpose of this study was to determine the optimal density of kissing gourami fry size 6.00±1.00 cm in a recirculation system. The research was carried out in November - December 2020 at the Basic Fisheries Laboratory, Aquaculture Study Program, Department of Fisheries, Faculty of Agriculture, Sriwijaya University. This research method used a completely randomized design (CRD), with 4 treatments of stocking density of kissing gourami, namely 2, 3, 4, and 5 fish L-1, respectively, which were carried out with 3 replications. The parameters observed included water quality, growth, survival rate, feed convertion ratio and blood glucose levels. The results of this study indicated that the best density was 1 fish L-1  with the water quality was 26.5 – 28.6oC for temperature, pH 5.9 – 7.4, dissolved oxygen 4.22 – 5.87  mg L -1 and ammonia 0.12 - 0.25 mg L -1, absolute weight growth was 0.90± 0.47 g, absolute length growth was 2.26± 0.17 cm, , survival rate was 100 %, FCR was 1.74, and blood glucose levels were 32.33 – 53.33  mg dL-1.  Key words : kissing gourami, production, recirculation, stocking density, water quality